Feasibility and Process Evaluation of a Need-Supportive Physical Activity Program in Aged Care Workers: The Activity for Well-Being Project - Lock, Merilyn; Post, Dannielle; Dollman, James; Parfitt, Gaynor (Frontiers in Psychology, 2020)
The need to undertake pilot testing and evaluation of novel health promotion programs has become increasingly apparent for the purpose of understanding the true effects of complex interventions and for testing and refining behavioral theories that these interventions are informed by. A mixed-methods process evaluation and feasibility study was undertaken for a need-supportive physical activity program that was piloted in a single-group pre–post study. The piloted program was designed to support participant needs of autonomy, competence, and relatedness through evidence-based and theory-informed behavior change strategies including a motivational interviewing style appointment, education on self-management tools (i.e., pedometers, goal setting, action and coping planning, a customized website for goal setting and self-monitoring), and self-determined methods of regulating physical activity intensity [affect, rating of perceived exertion (RPE), and self-pacing]. The program aimed to positively impact physical activity behavior, psychological well-being, and associated motivational processes. Reach, adoption, fidelity, context, change and performance objectives, and feasibility of the program were evaluated using information from survey respondents from the target population (n = 118) and implementing staff (n = 6); questionnaires from pilot study participants (n = 21); and individual semi-structured interviews with a combination of pilot study participants, non-participants, and implementing staff (n = 19). Process evaluation of the Activity for Well-Being program found that the reach of the program was moderate but adoption was low. The use of self-management tools and self-determined methods of regulating physical activity intensity appeared to be feasible. The website had mixed responses and low engagement. The element of having a support person elicited a strong positive response in the program participant interviews. Involving local implementing staff more directly into the delivery of the intervention could have potentially improved reach, adoption, and feasibility of the program.